Elucidation of material and mechanical properties on Bismuth Telluride nanocomposite film with graphene/nanocellulose inclusion - Abdul Rasyed, Amir Haziq (2024)
Thermoelectric (TE) is one of the interesting fields of study due to distinct characteristics on electrical energy generation from wasted heat retrieval. The focus on developing an improved TE-material especially in film condition has been crucial for enhanced applications in self-powered micro-devices. Bi2Te3 facing challenge in thermoelectric performance which not really fitted up and sustaining at its own micromechanical properties in film condition. Enhancement to improve the thermoelectric performance and increasing the micromechanical properties of the nanocomposite film with inclusions of graphene and CNF. The objective of this study is to enhance the micromechanical characteristics of Graphene-CNF/Bi2Te3 nanocomposite films. The process involves the addition of different amounts of carbon nanofibers (CNFs) into the nanocomposite using electrodeposition. The films are subsequently analysed to determine the surface morphology and composition. In the end, the micromechanical properties of the materials get evaluated to determine their mechanical performance. A succeed synthesis, effective diffused and coated in the film using -100mV pulsed deposition at ambient temperature determined by Cyclic Voltammetry analysis. The deposited carbon wt.% increased by approximately 10% comparing to the baseline reference of carbon wt.%. It determined that the deposition of CNFs increased as the weight percentage of carbon increased. Micromechanical properties are analysed using ultra-micro indentation device for evaluation of young’s modulus and hardness. This study achieve 100% higher compared to pristine Bi2Te3 of hardness and 34% increment of young’s modulus with inclusions of CNF. The advantage of CNFs has been verified through a comparison of Graphene-CNF/Bi2Te3 nanocomposite films containing different amounts of CNFs. In addition to the Hall-Petch effect, which restricts plastic deformation, the robust reinforcing impact of carbon nanofibers (CNFs) further enhances the mechanical properties.